Menggali Pemikiran Roger Bacon dalam Pendidikan Berbasis Eksperimen dan Metode Ilmiah - Fathoni, Tamrin; Muzamil, Muzamil; Rahman, Abdul; Rahmah, Nada Aini (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
The purpose of this study is to analyze Roger Bacon's thoughts on experimental education and scientific methods and their relevance in the context of modern education. This study uses a library method to analyze Roger Bacon's thoughts on experimental education and scientific methods, and their impact on the development of scientific education. By reviewing related literature, this study aims to explore the relevance of Bacon's thoughts in modern education, especially in the context of science and technology education. The result of Roger Bacon's thoughts is the development of education that is more based on experiments and scientific methods, which encourage direct observation and empirical verification. His ideas about the importance of critical thinking and the practical application of knowledge are relevant to the modern educational approach, which emphasizes project-based learning and experiments. Bacon's thoughts also lead to the simplification of the delivery of scientific knowledge, making it more accessible and understandable to the wider community.